How Should Shale Gas Extraction Be Taxed? - Daniel, Philip; Krupnick, Alan.; Matheson, Thornton; Mullins, Peter (Washington, D.C. : International Monetary Fund, 2017)
This paper suggests that the environmental and commercial features of shale gas extraction do not warrant a significantly different fiscal regime than recommended for conventional gas. Fiscal policies may have a role in addressing some environmental risks (e.g., greenhouse gases, scarce water, local air pollution) though in some cases their net benefits may be modest. Simulation analyses suggest, moreover, that special fiscal regimes are generally less important than other factors in determining shale gas investments (hence there appears little need for them), yet they forego significant revenues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet